Minat Siswa SMK dalam Melanjutkan Pendidikan ke Perguruan Tinggi - Wahidatuzzakiah Rahmadhani; Sudarman; Rahayu, Vitria Puri (Faculty of Teacher Training and Education, Mulawarman University, 2024)
The research in this thesis is motivated by the still low interest of vocational school students in continuing their education to tertiary institutions. Therefore, the focus of research in this thesis is how vocational school students are interested in continuing their education to college. This research aims to determine the interest of vocational school students in continuing their education to higher education at SMKN 1 Bengalon, East Kutai Regency. The type of research carried out was descriptive qualitative research. The informants in the research were class XII students. Data collection was carried out by direct observation and interviewing class XII students. Based on the research results, it shows that vocational school students' interest in continuing their education has increased. This can be seen from how students view career opportunities after graduating from college compared to just graduating from vocational school. Continuing education to college makes students believe that after graduating from college students will have greater opportunities in the field of work. Not only that, support from the surrounding environment influences the interest of students who want to continue their education and good academic aspects provide opportunities for students to be accepted at the desired university and study program.